Sistema de facturación electrónica y el impacto que esto tiene en las pequeñas y medianas empresas en sus procesos tecnológicos y mano de obra - Angarita Bedoya, Angélica Tatiana (Universidad Antonio Nariño, 2024)
This article is built in order to provide clarity regarding the implementation of electronic invoicing systems in Colombia, covering and specifying the processes of which this system is composed, starting because there are several fiscal documents that have been implemented with This mechanism for issuing digital information sent to the DIAN Directorate of National Taxes and Customs, it is common among people to believe that only electronic invoicing exists.